A New Construction of Multisender Authentication Codes from Pseudosymplectic Geometry over Finite Fields - Xiuli Wang (Journal of Applied Mathematics)
Multisender authentication codes allow a group of senders to construct an authenticated message for one receiver such that the receiver can verify authenticity of the received message. In this paper, we construct one multisender authentication code from pseudosymplectic geometry over finite fields. The parameters and the probabilities of deceptions of this code are also computed.